Introduction to biological physics for the health and life sciences - Franklin, Kirsten (John Wiley & Sons, 2019)
"The second large addition to the textbook is a new section in the Thermodynamics topic with chapters covering thermodynamic processes, heat engines, entropy, and thermodynamic potentials. The material presented in these chapters goes further into some thermodynamics concepts than is typical for a first-year physics text. However, students are confronted with concepts like entropy and Gibb's energy in other courses they undertake as part of their training. These students cannot be expected to develop a deep understanding of these ideas in a single semester, especially in a course whose main purpose is teach chemistry or biochemistry. Our primary goal in this section of the book is to provide students with a secondary source of information which they may access later in their course of study, though it may also prove useful in joining physics with chemistry in integrated science programmes"--